2017
DOI: 10.1021/acs.biochem.7b00175
|View full text |Cite
|
Sign up to set email alerts
|

A Single Outer-Sphere Mutation Stabilizes apo-Mn Superoxide Dismutase by 35 °C and Disfavors Mn Binding

Abstract: The catalytic active site of Mn-specific SOD (MnSOD) is organized around a redox-active Mn ion. The most highly-conserved difference between MnSODs and the homologous FeSODs is the origin of a Gln in the second coordination sphere. In MnSODs it derives from the C-terminal domain whereas in FeSODs it derives from the N-terminal domain, yet its side chain occupies almost superimposable positions in the two types of SODs’ active sites. Mutation of this Gln69 to Glu in E. coli FeSOD increased the Fe3+/2+ reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Catalytically active sites of both SODs contain three histidines and one aspartic acid that bind the metal ion co-factor (Figure 4A, left and middle panels). In addition, the Fe and Mn ions also bind to a solvent molecule (water or hydroxide) that is engaged in hydrogen bonds formation and, together with histidines and aspartic acid, participates in the coordination of either cation in an unusual distorted trigonal bipyramidal geometry around the metal center, as depicted in Figure 2B (128)(129)(130). Despite this remarkable similarity, most Fe-SOD and Mn-SOD enzymes are only functional when bound to their cognate metal ion (Table 1), illustrating their high specificity to metal co-factor (131)(132)(133).…”
Section: Cation Replacement Examples: Focus On Fe Mn and Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytically active sites of both SODs contain three histidines and one aspartic acid that bind the metal ion co-factor (Figure 4A, left and middle panels). In addition, the Fe and Mn ions also bind to a solvent molecule (water or hydroxide) that is engaged in hydrogen bonds formation and, together with histidines and aspartic acid, participates in the coordination of either cation in an unusual distorted trigonal bipyramidal geometry around the metal center, as depicted in Figure 2B (128)(129)(130). Despite this remarkable similarity, most Fe-SOD and Mn-SOD enzymes are only functional when bound to their cognate metal ion (Table 1), illustrating their high specificity to metal co-factor (131)(132)(133).…”
Section: Cation Replacement Examples: Focus On Fe Mn and Mgmentioning
confidence: 99%
“…4 A , left and middle panels ). In addition, the Fe and Mn ions also bind to a solvent molecule (water or hydroxide) that is engaged in the formation of hydrogen bonds and, together with histidines and aspartic acid, participates in the coordination of either cation in an unusual distorted trigonal bipyramidal geometry around the metal center, as depicted in Figure 2 B ( 126 , 127 , 128 ).
Figure 4 Structural properties of Mn-specific, Fe-specific, and cambialistic Mn/Fe-SODs.
…”
Section: Cation Replacement Examples: Focus On Fe Mn and Mgmentioning
confidence: 99%
“…In comparison to studying PCS effects, probing the SCS is often more challenging, as the latter typically induces more subtle electronic and structural perturbations and thus requires more careful experimental design and detailed characterization. Toward this goal, several studies have contributed to the advance of this field that include not only T1Cu proteins but also other redox-active proteins such as those containing purple Cu A center, iron and manganese superoxide dismutase, the heme-Cu B active site cytochrome c oxidase , and Fe-S proteins. , In previous publications, we have shown that E °′ of T1Cu azurin (Az) can be fine-tuned across a wide range of E °′ under physiological conditions, i.e., from −1 to +1 V vs standard hydrogen electrode (SHE) (all E °′ stated hereafter are vs SHE) by altering the hydrophobicity, hydrogen bond interactions, and the coordinated metals (Cu vs Ni) in the SCS of the T1Cu center. , The introduction of phenylalanine (Phe) to the SCS has been critical in accomplishing this tuning, as it allows the hydrophobicity of the T1Cu to be modulated. For example, the introduction of M44F and G116F to the N47S/F114N/M121L-Az variant resulted in an increase of E °′ from ∼690 to 970 ± 20 mV at pH 5.0, the highest E °′ of any engineered copper protein to date. , Despite these successes, the structural basis for such hydrophobicity-based redox tuning using Phe has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%